Development of polymerase chain reaction kit for detection of SARS-CoV-2 RNA in biological samples collected from animals - A. M. Timina; A. S. Yakovleva; M. V. Timanov; M. V. Biryuchenkova; Ye. S. Orlova (Ветеринария сегодня)
Today, global attention is drawn to the samecommon problem – spread of the novelCOVID-19 infection. From the end of December 2019 novelSARS-CoV-2 virus spreadover the majority of the countriesandon 11 March 2020 the World Health Organization announced pandemic. GlobalspreadofCOVID-19 was not limited to the human population and the rewasa need to test pet sand farm animals, whowere in contactwith the humans. The reare more and morere portson SARS-CoV-2 detected in minks, ferrets, dogs, cats, tigers, lions and other animals. Today the key methodofCOVID-19 diagnosis is polymerase chain reaction, butall currently availabletest-kits are intended for the virus detection in humans. The paper demonstrates data on the development of thereal-timePCR-basedmethodforSARS-CoV-2 RNA detection in the biological samples collected from animals. During the research, an optimal system of primers and aprobe were selected, reaction conditions were tested, basic validation specifications (sensitivity, specificity, reproducibility) wereset. The validation results demonstrated that the method met all the criteria of the high-quality measurement/test method sand it can be used for diagnostic tests. Thetest-kitwas based of the method in tended for SARS-CoV-2 RNA detection in animal biological samples and it was put into the veterinary practice. Animal populations in different regions of the Russian Federation were subjected to the screening tests in order to detect the novel coronavirus genome. NoSARS-CoV-2 was reported in her bivorous animals in the Russian Federation. TheFGBI “ARRIAH” experts detected only one positive pet animal.